STUDY KASUS PENDEKATAN INOVATIF FISIOTERAPI PEDIATRI: MENINGKATKAN KONSENTRASI ANAK AUTISME MELALUI INTERVENSI MIRROR GAMES - Utami, Inggrid Regita; Khasanah, Al Um Aniswatun; Sri Yuliana; Afifah, Zulaika Nur; Al Hazmi, Dhofirul Fadhil Dzil Ikrom; Yudistira, Efraldo; Yudistira, Bota Muhammad Akbar; Yudistira, Toumi Shiddiqi; Siamy, Hapy Ardiaviandaru; A.Zain, Afif Fairuz Fajri (Journal of Hospital Administration and Excellent Health Service, 2025)
Background: Autism or Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by two main symptoms: difficulties in social communication and interaction, as well as restricted and repetitive patterns of interests, activities, and behaviors. Children with autism often struggle to maintain concentration, which affects their ability to engage in learning and social activities. One therapeutic approach that can be used to improve concentration is mirror games, a mimicry-based activity involving both visual and motor interaction.Objective: To determine whether the mirror games method can improve concentration in children with autism.Research Method: This research used a single case study design, aimed at evaluating the effectiveness of physiotherapy management using the mirror games method to enhance concentration in a child with autism.Results: The results showed an increase in sustained attention duration and the ability to follow sequential instructions. The subject was able to maintain focus for a longer period and follow more instructions in sequence compared to before the intervention. This indicates that mirror games positively contribute to improving a child's concentration.Conclusion: The mirror games method can enhance concentration in children with autism and may serve as an enjoyable and practical alternative therapy that can also be applied at home.